THE INFLUENCE OF GREEN BANKING, INTELLECTUAL CAPITAL AND OPERATIONAL EFFICIENCY ON THE PROFITABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - kailun, Ilzania; Canggih, Clarashinta (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to analyze the influence of Green Banking, Human Capital, Structural Capital, Capital Employed, and Operational Efficiency on the profitability of Commercial Sharia Banks in Indonesia for the period 2021–2024. The study used quantitative methods with secondary data sourced from financial statements and bank sustainability reports. The sample was selected through purposive sampling, resulting in 12 Commercial Sharia Banks analyzed using panel data regression with a Fixed Effect Model (FEM). The results show that Green Banking and Operational Efficiency (BOPO) affect profitability, while Human Capital, Structural Capital, and Capital Employed do not. These findings indicate that the implementation of sustainable banking practices and effective operational cost management are key factors in improving the financial performance of Islamic banks, while intellectual capital still needs to be optimized to make a significant contribution to increasing company value.